1991
DOI: 10.1051/agro:19910701
|View full text |Cite
|
Sign up to set email alerts
|

Recherche de géniteurs de résistance à la fusariose de l'épi causée par Fusarium culmorum chez le blé et les espèces voisines

Abstract: Amélioration des plantes Recherche de géniteurs de résistance à la fusariose de l'épi causée par Fusarium culmorum chez le blé et les espèces voisines L Saur JY Morlais INRA, station d'amélioration des plantes, domaine de la Motte-au-Vicomte, BP 29, 35650 Le Rheu, France (Reçu le 21 décembre 1990; accepté le 29 avril 1991) Résumé — Sur une période de 10 ans, 230 variétés de blé tendre et 334 lignées appartenant à 15 espèces de triticinées ont été évaluées pendant une ou plusieurs années pour leur résista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…FHB severity was assessed at 350°C.d and 450°C.d after inoculation. The proportion of infected spikelets was recorded using a logarithmic scale from 1 (no disease symptoms) to 9 (spikes completely diseased) (Saur 1991;Ban and Suenaga 2000). Flowering time was recorded in all 3 years tested (1998, 1999, and 2000), and plant height was measured (to the tip of the spike, excluding awns) in 1999 and 2000.…”
Section: Plant Materialsmentioning
confidence: 99%
“…FHB severity was assessed at 350°C.d and 450°C.d after inoculation. The proportion of infected spikelets was recorded using a logarithmic scale from 1 (no disease symptoms) to 9 (spikes completely diseased) (Saur 1991;Ban and Suenaga 2000). Flowering time was recorded in all 3 years tested (1998, 1999, and 2000), and plant height was measured (to the tip of the spike, excluding awns) in 1999 and 2000.…”
Section: Plant Materialsmentioning
confidence: 99%
“…However, many backcrosses are needed to incorporate these exotic sources into adapted varieties, making this a long‐term strategy. An alternative short‐term approach has been to exploit moderate resistance already present in adapted material, as documented by Saur (1991) and Mielke (1980) Mapping studies based on spray inoculation in field conditions in ‘Renan’ × ‘Recital’ population, for example, revealed three stable QTLs from Renan on chromosomes 2B and 5A (Gervais et al, 2003), whereas Paillard et al (2004) reported two major QTLs from Arina from an Arina × Forno population on chromosomes 4A and 6D. However, the Arina × Forno map for chromosome 4A and 6D (Paillard et al, 2003) had two limitations: (i) the maps consisted of very few markers; and (ii) the flanking markers on either side of both chromosomes are RFLPs, which are not breeder‐friendly for high‐throughput molecular breeding strategies.…”
mentioning
confidence: 99%
“…However, many backcrosses are needed to incorporate these exotic sources into adapted varieties, making this a long-term strategy. An alternative short-term approach has been to exploit moderate resistance already present in adapted material, as documented by Saur (1991) and Mielke (1980). Mapping studies based on spray inoculation in field conditions in 'Renan' 3 'Recital' population, for example, revealed three stable QTLs from Renan on chromosomes 2B and 5A (Gervais et al, 2003), whereas Paillard et al (2004) reported two major QTLs from Arina from an Arina 3 Forno population on chromosomes 4A and 6D.…”
mentioning
confidence: 99%
“…The cultivation of genetically resistant cultivars is the most cost‐effective method to control the disease. Genetic variation for resistance to FHB is well documented in wheat and its relatives (Mesterhazy, 1983, 1995; Snijders, 1990a; Saur, 1991; Wilcoxson et al, 1992; Lemmens et al, 1993; Buerstmayr et al, 1996a, b). A general review of FHB on small grains has been published by Parry et al (1995) Breeding for resistance has been reviewed by Mesterhazy (1995) and Miedaner (1997)…”
mentioning
confidence: 99%